Insomnia - Robertson, Robbie (Crown, 2026)
"The rock legend tells the story of his wild ride with Martin Scorcese--as friends, adventure-seekers, and boundary-pushing collaborators--with all the heart of his New York Times bestselling memoir, Testimony. For three decades, Robbie Robertson has produced soundtracks for Martin Scorsese's films, a relationship that began when Robertson convinced Scorsese to direct The Last Waltz, the iconic film of the Band's farewell performance at the Winterland Ballroom on Thanksgiving 1976. The closing of the Band's story with that landmark concert opened a new door in Robbie Robertson's life--specifically the door to Scorsese's Malibu home. With both men on the outs with their wives, Robertson moved into Scorsese's place, inaugurating a two-year "lost weekend" of wild revelry and adventure. Though both men had already accomplished culture-changing feats, neither had reached thirty-five years of age, and each in his way stood at a creative precipice, searching for the beginning of a new phase of life and work. Their shared journey would take them around the world and down the rabbit hole of American culture in the long hangover of the seventies, a path lined with equal parts hedonism and paranoia, set against the backdrop of the disco-fueled streets of New York and the grand mansions of Mulholland Drive. With a cast of characters featuring Robert De Niro, Harvey Keitel, Sam Peckinpah, and many more, Insomnia is part comedy, part travelogue, echoing the blissed-out ride of Fear and Loathing as taken by two titans of American arts. Insomnia is an intimate portrait of a remarkable creative friendship, one that would explore the outer limits of excess and experience before returning to tell the tale"-- Provided by publisher.